FROM THE EDITOR - Lategan, Bernard C. (Scriptura, 1981)
Scriptura 5 is the second of our technical editions. The aim is to supplement regular issues with more technical papers on basic research in the field of Biblical Studies. By providing a forum for work of a more experimental nature, we hope to stimulate critical discussion and the exploration of new approaches.